Limited Facilities and Infrastructure as well as Mileage in Carrying out the Activities of the Medan Science Branch Organization - Cristina Asvera; Fauzi Kurniawan; Aliyyah Mahira Shafa; Felicya Nainggolan; Fitria Anjani; M.Rizky Fadillah; Mikael Togatorop; Naser Maulidina; Nisa Listiani; Rahmad Farraz; Ratih Syahfitri; Sofwatun; Yohanes Bagas (International Journal of Educational Practice and Policy, 2023)
The study is aiming to determine the organizational constraints of Medan Science in terms of facilities and infrastructure as a medium in achieving organizational goals. this type of research uses field research with qualitative descriptive methods. The data was collecting by using interviews technique. The study results shows that there were obstacles found included aspects of facilities and infrastructure such as the absence of a place for students to channel their interests and talents for example football fields, badminton, and a place to channel the creativity of Alwashliyah students and the long distance between organizational branches in increasing cooperation, and relationships in need hours of time.